Jurassic ammonites from the Muktinath region, central Nepal (Journal of Nepal Geological Society, 1982)
Three species of Oxfordian ammonites, Epimayaites aff. lemoini (Spath). Paryphoceras badiense Spath and Dichotomosphinctes subhelenae spath are described and figured from the Muktinath region of Central Nepal. They are all identified with the forms known from Cutch (=Kutch), and are the elements of Ethiopian "Province" of Hallam (1971).